High-Technology Subsidies in General Equilibrium: A Sector-Specific Approach - Karolina Ekholm; Johan Torstensson (The Research Institute of Industrial Economics (IUI), 1996)
We use a specific-factor model to examine the conditions under which policy-makers are able to increase aggregate production of high-tech goods by production or R&D-subsidies in the short and long run. The difficulties for the policy-makers in designing a subsidy scheme that succeeds in expanding aggregate high-tech production involve taking into account the trade-off between resources used in R&D and production of high-tech goods, the relative impact of different R&D activities on productivity, and the ease with which resources may be attracted from the non-high-tech sector of the economy to the various high-tech industries.
Keywords: F11; F12; 330; PRODUCTION; RESEARCH AND DEVELOPMENT; PRODUCTIVITY